Proceedings of the 2019 Conference on Empirical Methods in Natural Language Processing and the 9th International Joint Conferen 2019
DOI: 10.18653/v1/d19-1622
|View full text |Cite
|
Sign up to set email alerts
|

Question-type Driven Question Generation

Abstract: Question generation is a challenging task which aims to ask a question based on an answer and relevant context. The existing works suffer from the mismatching between question type and answer, i.e. generating a question with type how while the answer is a personal name. We propose to automatically predict the question type based on the input answer and context. Then, the question type is fused into a seq2seq model to guide the question generation, so as to deal with the mismatching problem. We achieve signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 11 publications
0
35
0
Order By: Relevance
“…• NQG-Knowledge [16], DLPH [12]: auxiliary-informationenhanced question generation models with extra inputs such as knowledge or difficulty. • Self-training-EE [38], BERT-QG-QAP [51], NQG-LM [55], CGC-QG [27] and QType-Predict [56]: multi-task question generation models with auxiliary tasks such as question answering, language modeling, question type prediction and so on.…”
Section: Evaluating Acs-aware Question Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…• NQG-Knowledge [16], DLPH [12]: auxiliary-informationenhanced question generation models with extra inputs such as knowledge or difficulty. • Self-training-EE [38], BERT-QG-QAP [51], NQG-LM [55], CGC-QG [27] and QType-Predict [56]: multi-task question generation models with auxiliary tasks such as question answering, language modeling, question type prediction and so on.…”
Section: Evaluating Acs-aware Question Generationmentioning
confidence: 99%
“…[27] jointly predicts the words in input that is related to the aspect of the targeting output question and will be copied to the question. [56] predicts the question type based on the input answer and context. [55] incorporates language modeling task to help question generation.…”
Section: Related Workmentioning
confidence: 99%
“…Du et al (2017) and Zhou et al (2017) followed the paradigm of sequenceto-sequence and showed promising results when combining rich features and attention mechanism. and Zhou et al (2019) incorporated answer-focused information to improve the relevance between answers and questions. Liu et al (2019) and Chen et al (2020) introduced graph networks to estimate significant contents in the source context.…”
Section: Related Workmentioning
confidence: 99%
“…In this paper, we categorized question types according to the interrogative words commonly used in general questions. Specifically, they are classified into 8 types -what, who, how, when, which, where, why and other (Zhou et al, 2019). We combine the contextual information s and the selector representation z as the input.…”
Section: Question Type Predictormentioning
confidence: 99%
“…Recent neural network-based methods have achieved promising results on QG, most of which are based on the seq2seq attention framework (Du et al, 2017;Gao et al, 2018;Kim et al, 2018;Zhou et al, 2019b), enriched with lexical features Sun et al, 2018;Song et al, 2018) or enhanced by copy mechanism (Du and Cardie, 2018;Sun et al, 2018;Zhou et al, 2019a).…”
Section: Sentencementioning
confidence: 99%